Pelaksanaan Pembelajaran Seni Budaya (Musik) Secara Daring Di Kelas IX.7 SMP Negeri 21 Padang - Reisha Fajriansi; Irdhan Epria Darma Putra (SENDRATASIK UNP, 2021)
This study aims to describe or reveal the implementation of online learning of cultural arts, especially music for students at SMP Negeri 21 Padang. The type of research used is descriptive qualitative research with the object of research is class IX students. The research instrument was the researcher himself and was assisted by supporting instruments, namely writing instruments and cellphones. Types of data sources in the form of primary data and secondary data, collected using data collection techniques in the form of literature study, observation, interviews, and documentation. Then there are 6 stages of data analysis techniques, namely collecting data in the field, identifying data, classifying data according to type, bringing up findings, describing data, discussing findings relevantly. The results of the study concluded that the implementation of online learning had not gone well as expected, because there were still many students who did not follow the online learning process. This is also due to the lack of understanding of students to understand the material through the online learning process, compared to the face-to-face process, where the teacher explains directly to students. So that students only understand the material themselves, are less involved or participate, because they are also just waiting for answers from friends and just waiting for what is conveyed by the teacher.